Bone health in functional hypothalamic amenorrhea: What the endocrinologist needs to know - Indirli, Rita; Lanzi, Valeria; Mantovani, Giovanna; Arosio, Maura; Ferrante, Emanuele (Frontiers in Endocrinology, 2022)
In the original definition by Klinefelter, Albright and Griswold, the expression “hypothalamic hypoestrogenism” was used to describe functional hypothalamic amenorrhoea (FHA). Given the well-known effects of estrogens on bone, the physiopathology of skeletal fragility in this condition may appear self-explanatory. Actually, a growing body of evidence has clarified that estrogens are only part of the story. FHA occurs in eating disorders, overtraining, and during psychological or physical stress. Despite some specific characteristics which differentiate these conditions, relative energy deficiency is a common trigger that initiates the metabolic and endocrine derangements contributing to bone loss. Conversely, data on the impact of amenorrhoea on bone density or microarchitecture are controversial, and reduced bone mass is observed even in patients with preserved menstrual cycle. Consistently, oral estrogen-progestin combinations have not proven beneficial on bone density of amenorrheic women. Low bone density is a highly prevalent finding in these patients and entails an increased risk of stress or fragility fractures, and failure to achieve peak bone mass and target height in young girls. Pharmacological treatments have been studied, including androgens, insulin-like growth factor-1, bisphosphonates, denosumab, teriparatide, leptin, but none of them is currently approved for use in FHA. A timely screening for bone complications and a multidisciplinary, customized approach aiming to restore energy balance, ensure adequate protein, calcium and vitamin D intake, and reverse the detrimental metabolic-endocrine changes typical of this condition, should be the preferred approach until further studies are available.